Pengaruh Literasi Keuangan, Sikap Keuangan, dan Financial Self-Efficacy terhadap Perilaku Pengelolaan Keuangan pada Kelompok Wanita Tani (KWT) Desa Mayong - Gusti Putu Adi Sucipto; Luh Indrayani (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aimed to examine the influence of financial literacy, financial attitude, and financial self-efficacy on financial management behaviour among members of the Women Farmers Group in Mayong Village, both partially and simultaneously. A quantitative approach with a causal research design was employed. The population of this study consisted of members of the Women Farmers Group in Mayong Village. The sample was determined using Slovin's formula with a simple random sampling approach, resulting in 84 respondents. Data were collected through questionnaires and analysed using multiple linear regression. Hypothesis testing was conducted using t-tests and F-tests with the assistance of SPSS version 25.0. The findings revealed that (1) financial literacy had a positive and significant influence on financial management behaviour among members of the Women Farmers Group in Mayong Village; (2) financial attitude had a positive and significant influence on financial management behaviour among members of the Women Farmers Group in Mayong Village; (3) financial self-efficacy had a positive and significant influence on financial management behaviour among members of the Women Farmers Group in Mayong Village; and (4) financial literacy, financial attitude, and financial self-efficacy collectively had a positive and significant influence on financial management behaviour among members of the Women Farmers Group in Mayong Village.